The Importance of Academic And Non-Academic Achievements In Improving The Quality of Education At Sd Negeri 1 Kranji - Dila Badilah Hasan (Jurnal Educatio FKIP UNMA, 2026)
This study aims to describe the advantages of academic and non-academic achievements in improving the quality of education at SD Negeri 1 Kranji. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that SD Negeri 1 Kranji had consistent achievements at the sub-district, district, and provincial levels, both in academic and non-academic fields, supported by effective school management through planning, organizing, implementing, and evaluating various student development programs. This success is supported by a structured coaching system, intensive teacher assistance, and cooperation between the school and parents. The achievements have a positive impact on improving the quality of education, shaping student character, and increasing public trust in the school.